2019
DOI: 10.1016/j.actbio.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial coating of spider silk to prevent bacterial attachment on silk surgical sutures

Abstract: Microbial infections from post-surgery or other medical-related procedure is a serious health problem. Nowadays, the research is focused on the development of new drug-free materials with antibacterial properties to prevent or minimize the risk of infections. Spider silk is known for its unique biomechanical properties allied with biocompatibility. Recombinant DNA technology allows to bioengineering spider silk with antimicrobial peptides (AMP). Thus, our goal was to bioengineered spider silk proteins with AMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 65 publications
0
65
0
Order By: Relevance
“…In 1998, Bickel et al reported a subcutaneous "spider silk" suture to address the thread easily break and discomfort of long incisions in patients, and there were no related complications within 10 years [56]. There is literature regarding the use of spider silk as an antibacterial coating on silk surgical sutures demonstrates to prevent bacterial attachment in the recent [57]. The overall reported of the above suggested the great benefits of natural spider silk as suture materials.…”
Section: Application Of Natural Spider Silkmentioning
confidence: 99%
“…In 1998, Bickel et al reported a subcutaneous "spider silk" suture to address the thread easily break and discomfort of long incisions in patients, and there were no related complications within 10 years [56]. There is literature regarding the use of spider silk as an antibacterial coating on silk surgical sutures demonstrates to prevent bacterial attachment in the recent [57]. The overall reported of the above suggested the great benefits of natural spider silk as suture materials.…”
Section: Application Of Natural Spider Silkmentioning
confidence: 99%
“…Finally, Franco et al. [ 25 ] published an innovative work using the dip‐coating technique to coat commercial silk suture threads. Bioengineered spider silk proteins with antimicrobial peptides (AMP 6mer‐HNP1) was used as an antibacterial drug‐free coating to decrease bacterial infections.…”
Section: Coating Of the Commercially Available Suture Threadsmentioning
confidence: 99%
“…Surgical site infection hast been assessed to arise in 5% of all medical procedures in hospitals [ 7 ], resulting in pain and discomfort for the patients and prolonged hospitalization and additional costs to the health system [ 8 ]. Not only implanted foreign bodies, yet also suture material have to be taken into consideration as a host for biofilm and therefore a potential source of infection [ 7 , 9 , 10 ]. In order to surmount this issue, the coating of suture material not only with chemicals such as triclosan [ 11 16 ], yet also with metal legions is not uncommon in medicine.…”
Section: Introductionmentioning
confidence: 99%